Risk factors of breast cancer in women at Sanglah General Hospital - Trisnadewi; I Made Sutarga; Dyah Pradnyaparamita Duarsa (Public Health and Preventive Medicine Archive, 2013)
Breast cancer is the most common cancer that found in women. More than 800,000 newly identified breast cancer cases are diagnosed in the whole world annually. In Indonesia, breast cancer is the second common cancer among women after servical cancer. Risk factors of breast cancer include pregnancy history, age at first pregnancy, breast feeding history, utilization of hormonal birth control, menarche history, genetic tendencies and past breast infections. This study aimed to assess the risk factors that contribute to increasing breast cancer incidence in cancer patients at Sanglah Hospital. Research used a matched paired case-control study with a sample of 38 female breast cancer patients and 38 female non-cancer patients with similar backgrounds, age and address. Data was collected through questionnaire. Data analysis was conducted using bivariate with McNemar test and multivariate analysis using logistic regression. The result of bivariate analysis showed that risk factors that increased breast cancer included breast disease history (OR=13.5; 95%CI: 3.21-56.77) and genetic tendencies (OR=8; 95%CI: 1.84–34.79). The result of multivariate analysis showed that the only significant risk factor was breast infection history (OR=43.19; 95%CI: 8.79-212.27). Future recommendations include increased health promotion about the importance of early detection and screening, as well as information related to the dangers of breast infection/disease. National policy regarding access to mammography facilities should also be prioritised.